Elimination of microcystin-LR and residual Mn species using permanganate and powdered activated carbon: Oxidation products and pathways - Jeong, bo young; Oh, Min-Seok; Park, Hyun-Mee; Park, Chanhyuk; Kim, Eun-Ju; Hong, Seok Won (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The oxidation of microcystin-LR (MC-LR) in deionized water (DI) and river water using potassium permanganate (KMnO4) at a neutral pH and at 23 +/- 2 degrees C was investigated. These two aqueous systems (i.e., DI and river water) gave comparable second-order rate constants (289.9 and 285.5 M(-)1s(-)1 (r(2) > 0.99), respectively), which confirmed the effectiveness of this oxidation process for the treatment of natural surface water. The presence of either humic or fulvic acid reduced the removal efficiency of MC-LR, with the latter exhibiting a greater inhibitory effect. Monitoring of MC-LR and residual Mn2+ levels with adding KMnO4 (1 mg/L) and powdered activated carbon (PAC, 5-20 mg L-1) before and during coagulation, respectively, revealed that 60 min of permanganate pre-oxidation followed by coagulant addition with PAC was the most effective approach for reducing both levels below limits stated by WHO guidelines. The MC-LR degradation products were the result of oxidation occurring at the diene and aromatic moieties of the Adda (3-amino-9-methoxy-2,6,8-trimethyl-10-phenyldeca-4,6-dienoic acid) side-chain, in addition to amine bond hydrolysis of the Mdha (N-methyldehydroalanine) moiety. Several toxic by-products with an intact Adda chain were observed during the reaction, but completely disappeared after 60 min. This further supports the conclusion that sufficient contact time with permanganate (i.e., >60 min) is essential to reducing the residual toxicity and maximizing the efficiency of MC-LR oxidation when treating raw water. (C) 2017 Elsevier Ltd. All rights reserved.